2018
DOI: 10.1155/2018/2746873
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Ameliorates Developmental Impairments of Rat Offspring with Prenatal Hyperhomocysteinemia

Abstract: Maternal high levels of the redox active amino acid homocysteine—called hyperhomocysteinemia (hHCY)—can affect the health state of the progeny. The effects of hydrogen sulfide (H2S) treatment on rats with maternal hHCY remain unknown. In the present study, we characterized the physical development, reflex ontogeny, locomotion and exploratory activity, muscle strength, motor coordination, and brain redox state of pups with maternal hHCY and tested potential beneficial action of the H2S donor—sodium hydrosulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 88 publications
(130 reference statements)
3
13
0
2
Order By: Relevance
“…The Paw Grip Endurance (PaGE) test demonstrated that in both groups (P10 and adults) the time spent on the grid was lower in hHCY rats indicating diminished muscle strength. These data are consistent with previously obtained data, where hHCY exerted detrimental effects on muscle force generation and fatigability (Veeranki et al, 2015; Majumder et al, 2018b; Yakovleva et al, 2018). The molecular mechanisms of detrimental effects of hHCY include mitochondrial dysfunctions, oxidative/endoplasmic reticulum (ER)‐stress and secretion of pro‐inflammatory cytokines (Veeranki et al, 2015; Majumder et al, 2018a).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Paw Grip Endurance (PaGE) test demonstrated that in both groups (P10 and adults) the time spent on the grid was lower in hHCY rats indicating diminished muscle strength. These data are consistent with previously obtained data, where hHCY exerted detrimental effects on muscle force generation and fatigability (Veeranki et al, 2015; Majumder et al, 2018b; Yakovleva et al, 2018). The molecular mechanisms of detrimental effects of hHCY include mitochondrial dysfunctions, oxidative/endoplasmic reticulum (ER)‐stress and secretion of pro‐inflammatory cytokines (Veeranki et al, 2015; Majumder et al, 2018a).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study we show how the transmitter release from the motor nerve endings, synapse morphology, muscle strength and redox status are modified in animals with prenatal hHCY. In our model of prenatal methionine‐based dietary hHCY the level of HCY is elevated not only in dams but also in their offspring suggesting an attractive approach to test the role of HCY in early development (Gerasimova et al, 2017; Yakovleva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased homocysteine levels during pregnancy result in preeclampsia, fetus pathologies or growth restriction due to endothelial dysfunctions of the placenta [ 27 ]. Prenatal hHcy induces well-known developmental impairments, including delay in reflex maturation or motor and cognitive dysfunctions [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, little is known about the long-term impact of prenatal hHcy.…”
Section: Introductionmentioning
confidence: 99%
“…Intracerebroventricular injection of homocysteine decreased the expression of CBS and CSE in the rat hippocampus and lead to learning and memory dysfunctions [ 35 , 36 ]. In our previous study H 2 S donor administration to female rats with hHcy during pregnancy restored the developmental impairment of the offspring during the first 3 weeks after birth [ 28 ]. The aim of the present study is to evaluate the effects of H 2 S donor on anxiety, motor and cognitive behavior, the level of oxidative stress in brain tissues, concentration of H 2 S, and the activity/expression of CBS in adult rats with maternal hHcy.…”
Section: Introductionmentioning
confidence: 99%